Impact of Interent Banking on Customer Satisfaction in Kathmandu - Lama, Padam Bahadur (Journal of Development Review, 2021)
This study examines the impact of internet banking on customer satisfaction in Kathmandu. Customer satisfaction is dependent variable. The independent variables are accessibility, convenience and service security. Research is conducted using primary data collecting opinions of 123 respondents from Kathmandu city. Structured questionnaire was adopted for the survey and Likert scale items were used for the collection of cross sectional. The correlation and regression are used to identify the association and impact of independent variable on customer satisfaction. The result shows that convenience has positive relationship with customer satisfaction which depicts that convenience in use of internet banking, higher would be the customer satisfaction. The service security has also positive correlation with customer satisfaction. It means better the service security of internet banking, higher would be customer satisfaction. The accessibility is also positively correlated with customer satisfaction. The regression result for the accessibility found not statistically significant.